Assessment of groundwater and surface water quality in a typical mining community: application of water quality indices and hierarchical cluster analyses - Emmanuella Anang; Meshack Tei; Anthony Boakye Antwi; Victor Kwabena Aduboffour; Benjamin Anang (IWA Publishing, 2023)
The rate at which freshwater sources are being contaminated by mining operations in the South-Western part of Ghana is alarming. However, no study has quantified the degree of contamination of the freshwater in such areas, leaving a gap in the literature that requires immediate attention. This study assessed the quality of the surface and groundwater in the Tarkwa Nsuaem Municipality. Even though the physical parameters such as pH and electrical conductivity were indicative of safe freshwater, other parameters such as turbidity, total suspended solids (TSS), dissolved oxygen (DO), and heavy metals in the water sources were high; thus, confirming possible leaching, runoff, and dissolution of the hazardous substances employed in the manganese mining operations. The water quality of 82% of the water sources along the Kawere Stream was low (Classes III and IV). Therefore, the local people are at risk of contracting water-related diseases, and health problems associated with the ingestion of Fe, As, and Mn. The findings in this study are important in establishing the rate at which mining operations are reducing the quality of freshwater in developing countries, and potentially affecting human health. HIGHLIGHTS The local people around the Kawere Stream depend more on groundwater due to the non-potable state of the stream.; The public health of the local people may be a major issue in the nearest future if the contaminants present in the groundwater are life-threatening.; 82% of the water sources are of poor quality.; Fe, As, and Mn contribute immensely to water contamination.; Indigenes are at risk of water-related diseases.;